2021
DOI: 10.1093/ntr/ntab147
|View full text |Cite
|
Sign up to set email alerts
|

History and Correlates of Smoking Cessation Behaviors Among Individuals With Current or Past Major Depressive Disorder Enrolled in a Smoking Cessation Trial

Abstract: Introduction Smoking among adults with major depressive disorder (MDD) is at least double that of the general U.S. population. More effective smoking cessation interventions for depressed smokers may be facilitated through a better understanding of the smoking and depression-related characteristics of this population. Methods We used baseline data from 300 participants enrolled in randomized clinical trial for smokers with cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…attempts. There also was variability in motivation to quit [74]. Only 53.0% of participants endorsed planning to quit in the next 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…attempts. There also was variability in motivation to quit [74]. Only 53.0% of participants endorsed planning to quit in the next 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of our study is that our sample was racially and socio‐economically diverse and spanned varied psychiatric presentations: 49.0% of participants had current MDD, 44.3% had other DSM diagnoses (including substance use disorder), only 27.3% were being treated for depression, and 16% reported one or more past suicide attempts. There also was variability in motivation to quit [74]. Only 53.0% of participants endorsed planning to quit in the next 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that about 40% of adults with depressive symptoms were current smokers, compared with those who were not depressed; further, individuals with depressive symptoms were more than twice as likely to be current smokers (Goodwin et al, 2017 ). Depressive symptoms are a barrier to the success of smoking cessation interventions (Quinn et al, 2022 ). In our sample, approximately one‐fourth of current smokers started smoking by the age of 19.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing current smokers for depressive symptoms helps prevent withdrawal symptoms. Depressive symptoms are an obstacle to the success of smoking cessation interventions [ 31 ]. Longitudinal studies are needed to clearly confirm the causal relationship between e-cigarette use and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%